Effect of Lateral Thinking Dispositions on Groupwork - ElaldÄ±, Åženel (Journal of Technical Education and Training, 2021)
The aim of this study is to compare the effect of lateral thinking dispositions on groupwork ---- in a collaborative learning environment from different angles as quantitatively and qualitatively in line with methodological pluralism. The population of the study included freshmen students studying Gastronomy and Culinary Arts in Tourism Faculty of a state university. The study was conducted in three samples within the scope of methodological pluralism including data triangulation (for SPSS analysis: N= 83- all the students in the study universe-; for thematic analysis: N= 66- selected on a voluntary basis depending on voluntary response sampling-; and for the Rasch analysis: N= 16 students accepting to participate this aspect of the study voluntarily and 3 faculty members who have the responsibilities of the groupwork of the students). In the quantitative phase, descriptive analysis was performed through the Rasch Measurement Model and SPSS program while in the qualitative part of the study, the case study approach was conducted under the checklist of COREQ Statement. Rasch results indicated the LATD (Lateral Thinking Dispositions) scores of the students graduating from tourism or cooking related vocational high schools and having work experience were higher than their counterparts not graduating from tourism related high schools and had no work experience beforehand. Qualitative results showed consistency with the quantitative results. Teachers are suggested to be trained so that lateral thinking skills can be implemented in class environment.